Hand lettering for beginners : simple techniques. endless possibilities - Ensign, Sarah (Alpha Books, 2021)
Learn how to use a brush pen, create basic strokes, and connect letters. Once you've honed your basic lettering skills, you'll learn how to draw fonts and compose quotes to create your own unique projects.